The Limits of Anti-Nuclear Critique in Pakistan - Sadia Tasleem; M. V. Ramana (Journal for Peace and Nuclear Disarmament)
Pakistan has a long history of social movements, some of which have challenged the military’s domination. However, apart from a short period after 1998 nuclear weapon tests by India and Pakistan, there has been limited opposition to nuclear weapons owned by the military. This paper examines one potential factor for this near absence: the intellectual arguments deployed by the main proponents of nuclear disarmament in Pakistan over the last 25 years. The post-1998 anti-nuclear critique in Pakistan has overwhelmingly focused on challenges pertaining safety and security, command and control, geopolitical imperatives of arms races, the operational limits of delivery systems like the short-range ballistic missiles and the risk of a nuclear war. We argue that such arguments inadvertently normalize nuclear weapons. Other arguments based on geopolitics make nuclear weapons appear inevitable in an anarchic world. Highlighting the consequences of a nuclear war has limited purchase in Pakistan where nuclear weapons are seen as the ultimate defense against all large-scale wars, nuclear and conventional. The alternative, we suggest, is to engage a broader critique focussed on the many ways in which nuclear weapons are implicated in everyday social and political life.